Some properties of starlike harmonic mappings - Aydoğan, Seher Melike; Yemişçi, Halime Arzu; POLATOĞLU, YAŞAR (Springer International Publishing Ag, Gewerbestrasse 11, Cham, Ch-6330, Switzerland, 2012)
A fundamental result of this paper shows that the transformation F=az(h(z+a/1+(a) over barz) + /(h(a) + <(g(a))over bar>(z + a) (1 + (a) over barz) defines a function in S0 HS* whenever f = h( z) + g( z) is S0 HS*, andwewill give an application of this fundamental result. MSC: Primary 30C45; Secondary 30C55
Keywords: harmonic starlike function; growth theorem; distortion theorem